Polityka ugody z caratem jako klucz do zachowania polskości : szkic do analizy myśli politycznej Włodzimierza Spasowicza (1829-1906) - Bryl, Maciej (2019)
Włodzimierz Spasowicz was a Polish social activist, literary critic and court attorney, born in Rzeczyca in the former Minsk Governorate, who spent most of his life in the Russian Empire. He started his journalistic career on the second half of XIX century in which he affirmed a conciliatory policy towards tsardom and Polish-Russian reconciliation. He was opposed to national uprisings, seeing in them only the defeat of the Polish nation. For many years he was associated with moderate liberals, he denied the policy of statism and state interference in social and economic life that was conducted at the beginning of the 20th century. As a liberal, he valued the good of the individual, not trusting the "rule of the people." As a model he indicated the decentralized state. In term of science his ideas were very interesting, but stayed completely isolated
Keywords: Imperium Rosyjskie; liberalizm; polityka ugody z caratem; Spasowicz, Włodzimierz (1829-1906).